Organization of University Corporate Interaction with Employers in the Process of Realization of the Basic Educational Programs - O. S. Gorlova; O. Yu. Kirillova; V. V. Nikulin (Управление)
The authors raise the issue of using the entrepreneurial approach in the implementation of major educational programs in higher education, offering to organize the process of interaction with the focus on one of the major groups of stakeholders of the educational organization – employers.